The Influence of Planning, Monitoring and Maintenance of Human Resources on Employee Performance Biogen BB Bogor - Ermiani, Ermiani; Indupurnahayu, Indupurnahayu; Amin, Akhmad Bakhtiar (CV. Strata Persada Academia, 2024)
Human Resource (HR) Planning is part of the management process that determines the movement of an organization's human resources from its current position to its desired position in the future. HR planning is closely related to the supervisory function because it can be said that planning is a standard or monitoring tool for the work being done. The HR maintenance function is also essential because employees are the assets (wealth) of every organization, and they always play an active role in determining whether or not the organization's goals are achieved. The research was carried out at BB Biogen Bogor. The research analyzes the influence of planning, monitoring, and Maintenance of Human Resources on Employee Performance. This research uses a survey method with a descriptive and causal approach. The sample used was 98 respondents. The research results show that Planning, Supervision, and Maintenance of Human Resources together have a real and positive influence with a contribution of 78.7%, and the remainder (21.3%) is influenced by other factors that are not central to this research.